The influence of finishing lines and margin location on enamel and dentin removal for indirect partial restorations: A micro-CT quantitative evaluation. (December 2022) - Mancuso, Edoardo; Mazzitelli, Claudia; Maravic, Tatjana; Pitta, João; Mengozzi, Alessandro; Comba, Allegra; Baldi, Andrea; Scotti, Nicola; Mazzoni, Annalisa; Fehmer, Vincent; Sailer, Irena; Breschi, Lorenzo
Abstract: Objectives: This in vitro research aimed to quantitatively evaluate the enamel and dentin tissue removal and the residual adhesion surface area (RAS) after different margin designs and locations for indirect partial restorations (IPR). Methods: A human molar was scanned using a Micro-CT and the STL file obtained was used to 3D-print 50 resin-tooth replicas. IPR standardized preparations were performed. The specimens were randomly assigned to 5 groups ( n = 10), according to preparation and margin location to the dental equator (DE): 1) Rounded shoulder above the DE (SA); 2) Hollow chamfer above the DE (CA); 3) Butt joint above the DE (BJ); 4) Rounded shoulder below the DE (SB); 5) Chamfer below the DE (CB). Then, the tooth replicas were scanned and each STL file was aligned and superimposed to the original STL model file. Data of enamel and dentin volume removal and RAS were assessed and statistically analyzed (one-way ANOVA and Kruskal-Wallis tests for the two dental substrates respectively). Significance was set at p <0.05. Results: Differences in dental tissue reductions were related to the margin location. Above the equator, SA, CA, and BJ performed comparably ( p >0.05). Below the equator, CB was significantly more conservative in enamel reduction than SB ( p <0.05) and showed the highest enamel adhesive surface exposure among the tested preparations ( p <0.05). Conclusions: When the preparation margin is placed above DE, BJ determines a greater exposure of dentin, reducing the adhesive surface in enamel. Below DE, SB seems to be more aggressive in terms of tissue removal compared to CB. Clinical Significance: The results of this in vitro study suggest that in teeth requiring partial restoration with the margin below the dental equator, a chamfer preparation would be more conservative than a shoulder preparation. When above the equator, preparations with flat designs would expose more dentine providing a worse substrate for adhesion.